Situs Judi Online Ilegal: Mengurai Implikasi Hukum dan Upaya Penegakan - Insani, Gema Mutiara; Farbadi, Mayla Putri; Azalia, Zatira Rahma; Nugroho, Andriyanto Adhi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Online gambling has become a growing phenomenon in Indonesia along with advances in information and communication technology. Even though gambling is generally prohibited in Indonesia, online gambling activities can still be accessed by the public through gambling sites from abroad. This journal outlines the legal implications of online gambling in Indonesia as well as law enforcement efforts that have been and will be carried out by the government to overcome this problem. Parties involved in online gambling, both organizers and players, may be subject to criminal sanctions in accordance with applicable regulations. Apart from that, online gambling is also related to issues of money laundering and consumer protection. The government has taken steps such as blocking online gambling sites, international cooperation, increasing public awareness, and law enforcement to overcome the rise of online gambling.